Islam-Based Listening Class Organitational Learning: Post Pandemi COVID 19 - AkbarJono, Ali; Serasi, Reko; Menti Ulan Dari, Anisa (GHAITSA : Islamic Education Journal, 2022)
This study aims to find out how the implementation of organizational learning in the post-covid-19 pandemic listening class at SMPN8 Kaur. This study uses a qualitative description method with an observation, interview, and documentation design. The researcher decided to conduct an interview with the eighth grade English teacher with two English teachers. From the results of the study, it was found that the English teacher at SMPN 8 Kaur had not implementation organizational learning in the listening class because the teacher in English at SMPN 8 Kaur had their own method of teaching. So, it can be concluded that the implementation of organizational learning in the listening class has not been applied by the teacher.